2020
DOI: 10.1039/c9se01307e
|View full text |Cite
|
Sign up to set email alerts
|

Engineering the structural formula of N-doped molybdenum carbide nanowires for the deoxygenation of palmitic acid

Abstract: The cleavage of C–O in palmitic acid is controlled by the self-assemblied MoxCNy nanowires with alterable structural formula.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…However, increasing the Ni content only results in increasing the Ni 2 Mo 3 N content other than increasing the Mo 2+∼δ+ content, suggesting that Mo 2+∼δ+ species is affected by Ni, C, and N simultaneously, which further proves that electron transfer within Ni-Mo-C-N catalysts exists and there is an interaction within the nickel molybdenum carbonitrides. As is well-known, XPS analysis is related to the surface properties of catalysts; thus, it can be concluded that Ni 0.30 MoCN exhibits a better oxidation resistance . It can also partly present the situation of Mo species among the carbonitride catalysts. It is well-known that Mo 2+∼δ+ species belongs to the carbonitrided Mo, which is related to the activity of the molybdenum-based carbonitrides.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…However, increasing the Ni content only results in increasing the Ni 2 Mo 3 N content other than increasing the Mo 2+∼δ+ content, suggesting that Mo 2+∼δ+ species is affected by Ni, C, and N simultaneously, which further proves that electron transfer within Ni-Mo-C-N catalysts exists and there is an interaction within the nickel molybdenum carbonitrides. As is well-known, XPS analysis is related to the surface properties of catalysts; thus, it can be concluded that Ni 0.30 MoCN exhibits a better oxidation resistance . It can also partly present the situation of Mo species among the carbonitride catalysts. It is well-known that Mo 2+∼δ+ species belongs to the carbonitrided Mo, which is related to the activity of the molybdenum-based carbonitrides.…”
Section: Resultsmentioning
confidence: 96%
“…As is well-known, XPS analysis is related to the surface properties of catalysts; thus, it can be concluded that Ni 0.30 MoCN exhibits a better oxidation resistance. 45 It can also partly present the situation of Mo species among the carbonitride catalysts. 46−50 It is well-known that Mo 2+∼δ+ species belongs to the carbonitrided Mo, which is related to the activity of the molybdenum-based carbonitrides.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the characteristics of fatty acid and ester hydrogenation, catalysts including noble metals, transition-metal phosphides, transition-metal suldes, and transition-metal carbides have been widely developed. [11][12][13][14] However, there are some problems with these catalysts, such as the deactivation in the case of transition metal suldes/carbides and the high cost of noble metals. Recently, transition-metal nitride has been widely studied due to the lower cost and Pt-like properties in HDO of biomass resources.…”
Section: Introductionmentioning
confidence: 99%
“…From Table 3, aliphatic compounds such as cetene and heptadecane were detected in the liquid e uent obtained a er gasi cation at 2 wt% feed concentration. Chen et al (2020) reported the catalytic hydrodeoxygenation via decarbonylation of palmitic acid to produce cetene as one of its intermediate products. Heptadecane is a product of stearic acid deoxygenation, along with carbon dioxide.…”
Section: E Ect Of Ni Catalyst and Feed Concentrationmentioning
confidence: 99%